Les applications de téléphones intelligents et tablettes pour l'investigation de scène de crime: état des lieux, typologie et critères d'évaluation. Issue 3 (2nd July 2016) - Baechler, Simon; Gélinas, Anthony; Tremblay, Rémy; Crispino, Frank
ABSTRACT: In recent years, applications for smartphones and tablets have undergone important developments, and their use is gradually becoming a new standard in everyday life and in some professional circles. Forensic science, and especially crime scene investigation, will not be an exception. However, should we expect a revolution of methods and practices, or only an extension of available tools without any fundamental change? To address this question and establish the current state of research and practice, this study considers a literature review, semi-structured interviews, and a survey of forensic unit representatives in Canada and Switzerland. It appears that there is at present no specific policy or framework to guide the development, use, and evaluation of applications that could support the investigation of crime scenes. Therefore, this article proposes a typology of applications and criteria for assessing their relevance, reliability, and response to operational requirements. The detailed study of five applications is used to illustrate the assessment process. A better understanding of issues and critical success factors associated with the use of applications is necessary to ensure the measured and intelligent integration of this technology in the daily investigation of crime scenes. In this regard, strengthening of scientific and pragmatic research that considers operational constraints is considered desirable.